Metabolomic Analysis Provides New Insight Into Tolerance of Huanglongbing in Citrus - Suh, Joon Hyuk; Tang, Xixuan; Zhang, Yi; Gmitter, Frederick G.; Wang, Yu (Frontiers in Plant Science, 2021)
There have been efforts to develop citrus cultivars that are tolerant of Huanglongbing (HLB), a catastrophic phloem-limited disease. Previous studies demonstrated continuous plant growth with phloem regeneration is one of the major characteristics of HLB tolerance. Here, metabolic mechanisms of HLB tolerance in citrus were elucidated using a multiple pathway-targeted metabolomics approach. Comparative analysis of healthy and infected HLB-tolerant and -sensitive mandarin cultivars (Citrus reticulata) revealed differentially expressed metabolic responses among different groups. Pathway enrichment analysis indicated aspartate and glutamate metabolism, purine metabolism, and biosynthesis of plant hormones were upregulated in the tolerant group, except salicylic acid signaling. Catabolic pathways linked to energy-yielding metabolism were also upregulated in the tolerant group. These metabolisms and pathways were interconnected each other, unveiling a pivotal metabolic network associated with HLB tolerance. In the network, auxins and cytokinins, plant hormones responsible for plant growth and phloem regeneration, were accumulated. In addition, purine metabolites serving as energy carriers and nitrogen sources of plants were increased. Only salicylic acid-related metabolites for plant defense responses were decreased in the tolerant group. Our findings may evidence the strategy of HLB-tolerant cultivars that sustains plant growth and phloem formation rather than displaying direct plant defense to overcome the disease.